Runtuhnya Global Governance: Saat Keluarnya AS dari Joint Comprehensive Plan of Action (JCPOA): The Collapse of Global Governance: When the US Leaves the Joint Comprehensive Plan of Action (JCPOA) - Yusa Djuyandi; Shafa Ghaisani Salsabila Brahmantika; Bima Riandy Tarigan (Society, 2021)
Global Governance encompasses the world’s political activities and the management of issues and phenomena that occurred on a nation-state, involving contributions from regional to the international environment. In the global security sector, there are numerous efforts carried out by a country to counter such external threats that can cause destabilization. Non-proliferation and nuclear developments for peace are such issues of the global defense-security concern. The attempts to control and ensure the use of nuclear has been carried out by enacting international law, resolutions, and multilateral agreements. The Joint Comprehensive Plan of Action (JCPOA) is one kind. Influencing the world’s security, politics, and economy, JCPOA began to be disrupted since the U.S. withdrawal as one of the parties that initially signed the agreement. This research aims to analyze The Collapse of Global Governance: When the U.S. Leaves the Joint Comprehensive Plan of Action (JCPOA). This research used a qualitative method with analysis based on secondary data, validated by the triangulation technique in this qualitative study. The analytical procedure uses secondary data from journals, media, and literature related to the Iran nuclear agreement and previous analyses discussing the U.S. exit from the JCPOA agreement. The analysis technique performs by arranging the data sequence, organizing the data into a pattern, category, and basic description. This research has found that Global Governance has fundamental weaknesses in its application. Through an analysis of the U.S. exit from the Iran nuclear agreement, it can be said that the reins of control are in the hands of the U.S. The Trump administration’s policy on behalf of the U.S. to leave JCPOA to thwart the achievement of Global Governance and significantly affects the multi-national economic, political, and security order. The implementation of Global Governance and the issues also raised based on the interests of the superpowers.